Employee performance enhancement through innovative behavior at PT KAI - Pujiyono, Muhammad; Harsono, Mugi (Management and Entrepreneurship: Trends of Development, 2020)
Human resource management cannot be separated from the factors of employees who are expected to perform as well as possible in order to achieve company goals. This research aims to examine the effects of individual characteristics and intrinsic motivation on innovative behavior and employee performance, and the influence of innovative behavior on employee performance. This research is quantitative analysis which obtains the sample data from 150 employees. Furthermore, the data is processed by Structural Equation Modeling (SEM) which assisted from the application program of Analysis of Moment Structure (AMOS) version 18.0. According to the  result of the analysis, it is concluded as the followings: an individual characteristic has a positive effect on innovative behavior; intrinsic motivation has a positive effect on innovative behavior; individual characteristics has a positive effect on employee performance; intrinsic motivation has a negative effect on employee performance and innovative behavior has a positive effect on employee performance.JEL Classification: M500, M510, M590